2003
DOI: 10.1016/s0014-5793(03)00149-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cDNAs from Japanese pufferfish (Fugu rubripes) and Atlantic salmon (Salmo salar) coding for homologues to tetrapod prion proteins

Abstract: We identi¢ed cDNAs coding for homologues to tetrapod prion proteins (PrPs) in Atlantic salmon (Salmo salar) and Japanese pu¡er¢sh (Fugu rubripes), which were termed 'similar to PrPs' (stPrPs). Besides signi¢cant sequence homologies the ¢sh stPrPs display characteristic structural features in common with tetrapod PrPs. In addition, two stPrPs were shown to be highly expressed in brain tissue. None of the so far identi¢ed PrP-homologues of ¢sh resembles doppel. Hence, the duplication of the PrP gene, which gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
2
32
0
3
Order By: Relevance
“…However, the yeast genome does not encode a structural homologue of PrP, making it difficult to carry out a complementation test of PrP activity in this organism. PrP homologues have been described in several nonmammalian species, including birds (69), frogs (70), turtles (71), and fish (72). Interestingly, the homologues from Xenopus laevis and Salmo salar lack the histidine-containing repeats that are postulated to bind copper in mammalian PrP (72), arguing against a universal role for copper in PrP function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the yeast genome does not encode a structural homologue of PrP, making it difficult to carry out a complementation test of PrP activity in this organism. PrP homologues have been described in several nonmammalian species, including birds (69), frogs (70), turtles (71), and fish (72). Interestingly, the homologues from Xenopus laevis and Salmo salar lack the histidine-containing repeats that are postulated to bind copper in mammalian PrP (72), arguing against a universal role for copper in PrP function.…”
Section: Discussionmentioning
confidence: 99%
“…Turchini et al (2009) report that there is no documentation of fish disease outbreaks associated with the transmission of fish pathogens via fish meal and fish feed. Oidtmann et al (2003) have, however, shown that fish have DNA that codes for the production of prion proteins and thereby theoretically can produce prion diseases such as transmissible spongiform encephalopathies (TSE). Hence, intra-species recycling of feed resources is currently prohibited in Europe (European Commission 2003b).…”
Section: Species From Lower Trophic Levelsmentioning
confidence: 99%
“…The preliminary structure of PrP is diverse; however, PrP from different sources shows the conservative structures including a signal sequence, an N-terminal repetitive region, a highly conservative hydrophobic region, a C-terminal globular domain consisting of two β-sheets and three α-helices, and a disulfide bond and a glycosyl phosphatidylinositol (GPI) anchor site (Suzuki et al, 2002;RiveraMilla et al, 2006). PrP encoding gene has been cloned and characterized from diverse organisms including mammals (Wopfner et al, 1999), birds (Gabriel et al, 1992), reptiles (Simonic et al, 2000;Oidtmann et al, 2003), and amphibians (Strumbo et al, 2001), and diverse fish species such as Atlantic salmon (Salmo salar) (Oidtmann et al, 2003), stickleback (Gasterosteus aculeatus) (Oidtmann et al, 2003), zebrafish (Danio rerio) (Cotto et al, 2005), Japanese sea bass (Lateolabrax japonicus) and Japanese flounder (Paralichthys olivaceus) (Liao et al, 2005), common carp (Cyprinus carpio) and trout (Oncorhynchus mykiss) (Premzl and Gamulin, 2007), and sea bream (Sparus aurata) (Favre-Krey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%